ACVIM Consensus Statement on Therapeutic Antimicrobial Use in Animals and Antimicrobial Resistance. (17th March 2015) - Weese, J.S.; Giguère, S.; Guardabassi, L.; Morley, P.S.; Papich, M.; Ricciuto, D.R.; Sykes, J.E.
Abstract : The epidemic of antimicrobial resistant infections continues to challenge, compromising animal care, complicating food animal production and posing zoonotic disease risks. While the overall role of therapeutic antimicrobial use in animals in the development AMR in animal and human pathogens is poorly defined, veterinarians must consider the impacts of antimicrobial use in animal and take steps to optimize antimicrobial use, so as to maximize the health benefits to animals while minimizing the likelihood of antimicrobial resistance and other adverse effects. This consensus statement aims to provide guidance on the therapeutic use of antimicrobials in animals, balancing the need for effective therapy with minimizing development of antimicrobial resistance in bacteria from animals and humans.